The role of self-perceived age in older adults considering adjuvant chemotherapy. Issue 2 (March 2023) - Yilmaz, Sule; Koita, Fatoumata; Zittel, Jason; Wells, Megan; Mohile, Supriya; Wittink, Marsha; Kelly, J. MacLaren; Sedrak, Mina; DeCaporale-Ryan, Lauren; DiGiovanni, Grace; Magnuson, Allison
Abstract: Introduction: Aging-related concerns can increase the risk of treatment toxicities among older adults considering adjuvant chemotherapy. We previously demonstrated that older adults with cancer who reported feeling older than their chronological age (i.e., self-perceived age) were more likely to have aging-related concerns identified during a geriatric assessment. We explored how decisions about adjuvant chemotherapy vary with or are related to older adults' self-perceived age. Materials and Methods: We conducted a secondary analysis of a multi-phased feasibility pilot using semi-structured interviews that were conducted to explore the patient decision-making process for adjuvant chemotherapy. Interviews incorporated questions about chronological and perceived age as factors for decision-making. Patient eligibility for the study included (1) age ≥ 70 years and older, (2) a diagnosis of breast, colon, or lung cancer and considering adjuvant chemotherapy, and (3) able to read size 18 font in English. Interview data were analyzed using constant comparative method. Results: Twenty-one patients were enrolled. The mean chronological age was 78 years (range 71–91). The average perceived age of patients was 57 years (range 21–80). Eleven patients chose to receive treatment while ten patients did not. Aging-related themes illustrated that self-perceived age plays an important role when patients make decisions about adjuvant chemotherapy. More specifically, patients who reported their self-perceived age as younger than their chronological age also reported better perceived health status and chose to receive adjuvant chemotherapy. Discussion: Patients' experiences of aging and self-perceived age may have different implications for decision-making.